Information, physics, and computation - Mezard, Marc.; Montanari, Andrea (Oxford : Oxford University Press, 2009)
A very active field of research is emerging at the frontier of statistical physics, theoretical computer science/discrete mathematics, and coding/information theory. This book sets up a common language and pool of concepts, accessible to students and researchers from each of these fields.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Statistical physics; Coding theory; Computer science